Development and implementation of a system of quality costs in a company of the automotive sector that allows you to detect and quantify opportunities for improvement - Lozano Taylor, José (2014)
In this study, we proposed to implement a system of quality cost. The system is based on the quantification of the monetary costs of prevention, assessment and failures that allows making an objective decision with respect to the priority of the problems to solve. It also allows to change the quality culture of the company personnel based on a change in the perspective of the consequences that daily problems do, and to have bases for a more objective comparison with other units of the company and with regard to competition. Detail arising in the development of the quality system in a pilot area of a company in the automotive industry will allow to view with objectivity the benefits and difficulties of this type of systems.